Theater practice and interpersonal synchronization behaviors: a pilot study comparing actors and non-actors - Sofia, Gabriele; Mager, Clément; Brunel, Lionel; Noel, Anne-Sophie (Frontiers in Human Neuroscience, 2024)
Recent studies in the field of theater studies no longer view theater as an object, but rather as a dynamic relationship between actors and spectators. In an embodied and situated perspective of cognition, imagination emerges as a product of this dynamic. This study aims to investigate whether acting practice enhances someone's abilities to set up an effective relationship with others and allows the individual to better manage not only the relationship itself, but also her/his own feelings and those of her/his partner. 82 healthy Italian adults, with no communication disorders, including 43 actors (Mage = 25.4 ; S.D = 3.64) and 39 non-actors (Mage = 24.1 = S.D = 4.17) completed a joint verbal production task named Random Sequence Generation (RSG) task. Initially, participants performed the task individually. Subsequently, in a second phase, they worked in pairs with another participant, taking turns to contribute to a shared sequence. Pairings were predetermined to ensure a balanced mix of actors and nonactors, and to prevent participants from having prior relationships. Following the task, subjects were queried about their sense of presence, and, their perception of entitativity with their partner. We observed a replication of Towse's (2016) findings, showing higher RSG scores and reduced repetition in the paired condition, indicative of coupling and synchronization behavior. Within pairs, the level of the sense of presence of both partners was positively correlated. Furthermore, an interaction effect between the sense of presence and acting experience on the perception of entitativity was observed. Specifically, actors described perceived entitativity with their partners when their sense of presence was heightened, whereas non-actors experienced a decrease in perceived entitativity with their partners under similar circumstances. We discuss the results and limitations of the study, suggesting the effect of artistic practice on the development of a sort of dual-task ability which enables actors to organize their sensations and actions while sustaining a meaningful connection with others. This research represents an interdisciplinary collaboration between theater studies and cognitive sciences, highlighting the value of a multidisciplinary approach to research.